Pengaruh Video Dakwah Youtub Terhadap Pembentukan Akhlakul Karimah Mahasiswa Manajemen Dakwah IAIN Parepare - Nur Hafifa; Firdaus Muhammad; Arifuddin Tike (Danudirja Setyabudi Nusantara, 2025)
The purpose of this study is to analyze the usage patterns and influence of Islamic preaching videos on YouTube on the formation of noble character among Da'wah Management students at IAIN Parepare. This research employs a survey method with a quantitative approach. Data collection utilizes questionnaires. The population in this study consists of 104 students, and the sampling technique used is total sampling method, where all members of the population serve as samples, totaling 104 students from the 2022 to 2024 cohorts. The research location is at IAIN Parepare among Da'wah Management students. The data analysis techniques employed include simple linear regression test, correlation test, and coefficient of determination analysis test. The research findings indicate that the majority of students tend to watch Islamic preaching videos regularly. The level of student attention toward Islamic preaching videos reaches 78.5%, demonstrating that they not only watch but also pay attention to the content presented. Furthermore, 78.65% of students acknowledge internalizing the Islamic preaching content in the videos they watch, reflecting emotional engagement and understanding of the values conveyed. The frequency of watching Islamic preaching videos is recorded at 71.16%, while the viewing duration reaches 71.25%, indicating that this activity has become part of their religious and spiritual routine. Variations in frequency and duration depend on individual interests and each student's spiritual needs.Based on the calculated t-value of 2.881, which is greater than the table t-value of 1.983, H₀ is rejected and Hₐ is accepted. Meanwhile, the significance value of 0.005 < 0.05 indicates that the Islamic preaching video variable influences the formation of noble character (Y). The implications of this research encompass both practical and theoretical aspects. From a practical perspective, it is hoped that Da'wah Management students at IAIN Parepare can use YouTube social media wisely and consider the benefits of using YouTube as a medium for Islamic preaching. From a theoretical standpoint, the results of this research can be used as a reference in developing effective and efficient preaching programs for Da'wah Management students.